Health-related quality of life in parents of adolescents one year into the COVID-19 pandemic: a two-year longitudinal study - Gudrun Rohde; Sølvi Helseth; Siv Skarstein; Milada Småstuen; Hilde E. T. Mikkelsen; Kristin Haraldstad (Health and Quality of Life Outcomes, 2022)
Abstract Aim For many adults, their role as a parent is a vital part of their life that may influence their health-related quality of life (HRQOL) and vary with the age of their child. The aim of the present study was to describe and compare sociodemographic and psychological factors, pain and HRQOL in parents of adolescents assessed at baseline and 2 years later,—during the COVID-19 pandemic. Methods A longitudinal study of 309 parents from the general Norwegian population was conducted. The parents were chosen based on their adolescent’s school belonging and responded to a web-based questionnaire. We used data collected at baseline (T1), when the adolescents were aged 14–15 years (2018/2019), and two years later (T2), in 2021, when the COVID-19 pandemic was ongoing. The response rate was 55%. HRQOL was assessed using RAND-36. Data were analysed using McNemar tests, paired samples t-tests and multiple linear regression analyses. Results Of the participants, 82% were mothers and 18% fathers. From T1 to T2, the average pain score increased, 1.6 (95% CI [-1,4; 1.8]) vs 1.8 (95% CI [1,6; 2.0]), the pain interference emotion score increased, 1.6 (95% CI [1.3; 1.9]) vs 1.8 (95% CI [1.5; 2.1]), and a larger proportion reported pain duration > 3 months (44% vs 50%, p = 0.014). The parents were more lonely, 12.8 (95% CI [12.3; 13.3]) vs 13.7 (95% CI [13.2; 14.2]), and reported lower RAND-36 mental component summary (MCS) scores, 52.2 (95% CI [51.3; 53.2]) vs 50.9 (95% CI [49.8; 52.0]). There were no significant associations between gender, sociodemographic factors, psychological factors, pain at T1 and changes in RAND-36 physical component summary (PCS). A positive change in MCS from T1 to T2 was predicted by working part time, B = 5.22 (95% CI [1.05; 9.38]) (ref no paid work) and older age, B = 0.24, (95%CI [-001; 0.42]), and there was a negative change with stress, B = -17.39, (95%CI [-27.42; -7.51]). Conclusion The parents experienced more pain and were lonelier, and more reported reduced mental HRQOL. However, the changes appear to be of limited clinical significance.